2000
DOI: 10.1128/jcm.38.9.3515-3517.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycobacterium neoaurumIsolated from a Neutropenic Patient with Catheter-Related Bacteremia by 16S rRNA Sequencing

Abstract: A rapidly growing pigmented mycobacterial strain with an ambiguous biochemical profile was isolated from the blood culture taken through the Hickman catheter of a 9-year-old girl with acute lymphoblastic leukemia. Whole-cell fatty acid analysis showed that the best match profile was that of Mycobacterium aurum, but the similarity index was only 0.217, meaning that there were no good matches between the isolate and the organisms in the database of the Microbial Identification System. The 16S rRNA gene of the my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…With the whole genome sequencing data of more than 100 bacteria and archaea available, it has been noted that there are relatively small interoperon heterogeneities for 16S rDNAs. In our experience in 16S rDNA sequencing, both for the known species and novel genera and species, direct sequencing of the PCR products has always been successful (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). In this study, when we first amplified the 16S rDNA of HKU15 T and sequenced the PCR product directly, it was repeatedly observed that the 5' end of the PCR product could not be sequenced clearly, with the presence of multiple peaks.…”
Section: Discussionmentioning
confidence: 85%
“…With the whole genome sequencing data of more than 100 bacteria and archaea available, it has been noted that there are relatively small interoperon heterogeneities for 16S rDNAs. In our experience in 16S rDNA sequencing, both for the known species and novel genera and species, direct sequencing of the PCR products has always been successful (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). In this study, when we first amplified the 16S rDNA of HKU15 T and sequenced the PCR product directly, it was repeatedly observed that the 5' end of the PCR product could not be sequenced clearly, with the presence of multiple peaks.…”
Section: Discussionmentioning
confidence: 85%
“…1 Furthermore, non-cultivable organisms and organisms with ambiguous biochemical profiles can be classified and identified. 2 3 Recently, we have reported the use of this technique for the identification of bacterial strains with ambiguous biochemical profiles, [4][5][6][7][8] species that are rarely encountered clinically, [9][10][11][12][13] and a bacterium that is non-cultivable 14 ; the discovery of a novel clinical syndrome 15 16 and two novel species 17 18 ; and the characterisation of β haemolytic Lancefield group G streptococcal bacteraemia 19 and thermotolerant Campylobacter fetus bacteraemia. 20 "The 16S rRNA gene is highly conserved within a species and among species of the same genus, and hence can be used as the new gold standard for speciation of bacteria"…”
mentioning
confidence: 99%
“…Pigmented rapidly growing mycobacteria are normally not known to cause disease. However, M. neoaurum, a pigmented rapid grower, has been associated previously with several cases of catheter-related bacteremia and has been best identified using 16S rRNA gene sequencing (25). Definitive identification of these species is difficult without advanced methods such as HPLC or sequencing.…”
Section: Discussionmentioning
confidence: 99%